An Inquiry into Turkish Academicians’ Willingness to Communicate in English - Kenan Çetin; Ferit Kılıçkaya (Nalans, 2019)
Willingness to communicate concept has caught the interest of many studies in the field of second language acquisition. Although studies which examine relationship between WTC and foreign language proficiency can be found in the literature, all of them were conducted with the participation of university students; therefore, this study aims to examine the WTC levels of the academicians working at Faculties of Education in Turkey, and the relationship between their willingness to communicate and proficiency as determined by YDS (Foreign Languages Examination). Another aim of this study is to obtain the views of the academicians towards their willingness to communicate in English and explore the factors affecting it. A total number of 450 (53.1% female and 46.9% male) academicians working at the faculties of education different parts of Turkey participated in the questionnaire which was administered online and from these participants eight (three female and five male) of them participated in the interviews. In the light of the study, personal and situational factors affecting the academicians’ willingness to communicate are presented.